Pengembangan Game Interaktif Ular Tangga berbantuan Genially untuk Meningkatkan Hasil Belajar pada Materi Gotong Royong di Sekolah Dasar - Annisa Apriyanti; Lina Novita; Santa (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Learning activities in elementary schools are expected to encourage students’ active participation; however, classroom instruction is often still dominated by conventional teaching methods, resulting in low student engagement and less optimal learning outcomes. Therefore, innovative and interactive learning media are needed to create a more meaningful learning experience while improving students’ understanding of the topic of Mutual Cooperation. This study aims to develop a Genially-assisted Interactive Snakes and Ladders Game on the topic of Mutual Cooperation for fourth-grade elementary school students, determine the feasibility of the media, and examine the effectiveness of the media on students’ learning outcomes. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. Data collection techniques included observation, interviews, questionnaires, documentation, as well as pretest and posttest assessments. The data were analyzed using descriptive quantitative analysis and N-Gain calculations. The results showed that the Genially-assisted Interactive Snakes and Ladders Game was categorized as highly feasible based on validations conducted by media experts, material experts, and language experts. Students’ learning outcomes also improved, as indicated by higher posttest scores compared to pretest scores, with an N-Gain result in the high category, indicating that the media was effective for use in learning activities. Therefore, the Genially-assisted Interactive Snakes and Ladders Game can be used as an alternative interactive learning media in elementary schools.